Perspective - from describing to understanding environment-physiology relations: 50th birthday of a branch in ecophysiology - Schwarzbaum, Pablo Julio (2011)
Animals generally show various adaptation features that render them fit for survival in their specific environment or, turned the other way round, specific environments can only be inhabited by animals that have developed corresponding adaptations. While this seems obvious nowadays to every biologist, 50 years ago this concept still needed to be validated for each specific case. In a brief historical perspective we highlight an outstanding example of an article where such environment–physiology relations have been examined in detail and where in fact the foundations of a new branch in ecophysiology have been established, the Ecophysiology of the Marine Meiofauna.